PENGARUH ORIENTASI HUBUNGAN DAN ORIENTASI TUGAS DALAM KEPEMIMPINAN TERHADAP KINERJA PELAKU USAHA - Sidharta, Iwan; Lusyana, Dina (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
Effective leadership is a determining factor in the success of businesses, especially SMEs. By doing effective leadership will result in optimal performance for SME. the center of clothing in Bandung is one of the leading sectors of the local government of Bandung which is expected to provide economic impact for the community and the government. The purpose of this study was to determine the influence of factors that affect leadership based on a relationship oriented and task oriented towards performance Sentra business communities in the center of clothing Bandung. Exploratory research methods of data analysis techniques using Structural Equation Modelling (SEM), component-based Partial Least Squares (PLS). The number of respondents as many as 54 SMEs with data collection data collection technique purposive sampling. Results of the study indicate where relationship oriented and task oriented significant effect on the performance of SMEs in the center of clothing. Keywords: relationship oriented; task oriented; performance